Impact of the COVID-19 Pandemic on Acute General Surgical Admissions in a District General Hospital in the United Kingdom: A Retrospective Cohort Study. (12th August 2020) - Callan, Rory; Assaf, Nazrin; Bevan, Katharine
Abstract : The COVID-19 pandemic of 2020 has greatly impacted healthcare systems and society more generally around the world. The management of patients infected with SARS-CoV-2 has primarily impacted emergency departments, medical teams, and intensive care units. However, the impact on health systems as a whole, including surgical specialties, has been wide ranging. We aimed to establish the impact of the COVID-19 pandemic and associated lockdown on the number and characteristics of general surgical patients reviewed and/or admitted by the surgical team within a district general hospital. We performed a retrospective cohort analysis of patients admitted in the 2-week period from start of the lockdown (Monday 23rd March 2020 to 5th April 2020), and the same period 1 year earlier (Monday 25th March 2019 to 7th April 2019). Number of patients reviewed and admitted were compared between the two cohorts. Data including diagnosis, operation/procedural interventions, and length of stay were analysed. The overall number of patients reviewed and admitted by the surgical team was substantially lower during the period of lockdown (61 vs 126). Of the patients seen during lockdown, a smaller proportion were admitted to hospital after initial surgical review (59% vs 77%, p < 0.05 ). Interventional/operative procedures were performed in a similar proportion of patients in both cohorts (31%). Our data show that there has been a substantial reduction in the number of patients being referred to and admitted by the general surgical team at our centre during the COVID-19 pandemic. Explanations for this include reduced attendance due to risk perception of the patients, the impact of lockdown messages and advice regarding self-isolation, as well as an increased threshold for patient admission during the COVID-19 pandemic. Key learning points include the possible benefits of a reduction in admission to hospital of patients with nonurgent conditions.